The “Public” of Richard Hooker’s Book 7 of the Laws: Stitching Together the Unjoined - Almasy, Rudolph P. (Renaissance and Reformation / Renaissance et Réforme, 2018)
This article begins with the notion that a text can create and influence a “public,” that is, a group of individuals with common values and aspirations. Richard Hooker’s Of the Laws of Ecclesiastical Polity (1594–1662) is the focus here; specifically, this article shows how book 7, which defends the prelacy, stitches together civil and ecclesiastical governors throughout the commonwealth in order to persuade this public not to embrace a Presbyterian ecclesiology and rid England of its bishops. Accordingly, Hooker’s text, composed with this public in mind, links together the nature and role of the civil and ecclesiastical by arguing that both are “of God,” by giving his public the intellectual skills to understand his defense of bishops, and by concentrating on public authority, public wisdom, and the public good which the magistrates must protect. Hooker’s goal is to encourage various estates to understand the threat to their power by the Presbyterian call for change. The hope is that the magisterial community, which runs the country and includes bishops, will consider the whole of the commonwealth and the value of the status quo before joining with the Presbyterians for change.